BABAD DALEM SUKAWATI DAN GEGURITAN BABAD DALEM SUKAWATI: ANALISIS RESEPSI - Suantara, I Putu Eka (Humanis, 2014)
The research of “Babad Dalem Sukawati and Geguritan Babad Dalem Sukawati: Analysis Reception” aims to describe the narrative elements of Babad Dalem Sukawati and how Babad Dalem Sukawati was receipted in Geguritan Babad Dalem Sukawati. The theory applied in the present research was the structural theory proposed by Teew (1984), supported by Sutrisno (1983), Luxemburg (1984), Hutagalung (1975), and Pradotokusumo (1986). The theory referred to the concept which was related to the structure of belles-lettres. To analyze Babad Dalem Sukawati receipted in Geguritan Babad Dalem Sukawati the writer implemented the reception approach referring to the opinion of Junus (1985), Fokkema (1977), and Suwardi (1979). Script reading method was used in the data collecting stage and was supported with retroactive and translating techniques which was continued by holding interview method supported with noting technique. The analysis stage applied hermeneutic and qualitative methods with descriptive-analytical technique. The analysis results were presented by formal and informal methods supported with deductive and inductive techniques, then the comparing method was used supported with tabulating technique. The result gained in the present study of Babad Dalem Sukawati and Geguritan Babad Dalem Sukawati was the existence of the formation structure. The formation method includes the plots, the settings, the characters and characterizations, the theme, and the values. Babad Dalem Sukawati that was receipted in Geguritan Babad Dalem Sukawati was regarded to the realtions between those two scripts, the relations intended were the relations the plots, the settings, the characters and characterizations, the theme, and the values.
Keywords: Babad, Geguritan, structure, and resepsi.